Strategies to improve patient retention on antiretroviral therapy in sub-Saharan Africa - Harries, Anthony D (Blackwell Publishing Ltd, 2010)
The scale-up of antiretroviral therapy (ART) has been one of the success stories of sub-Saharan Africa, where coverage has increased from about 2% in 2003 to more than 40% 5 years later. However, tempering this success is a growing concern about patient retention (the proportion of patients who are alive and remaining on ART in the health system). Based on the personal experience of the authors, 10 key interventions are presented and discussed that might help to improve patient retention. These are (1) the need for simple and standardized monitoring systems to track what is happening, (2) reliable ascertainment of true outcomes of patients lost to follow-up, (3) implementation of measures to reduce early mortality in patients both before and during ART, (4) ensuring uninterrupted drug supplies, (5) consideration of simple, non-toxic ART regimens, (6) decentralization of ART care to health centres and the community, (7) a reduction in indirect costs for patients particularly in relation to transport to and from clinics, (8) strengthening links within and between health services and the community, (9) the use of ART clinics to deliver other beneficial patient or family-orientated packages of care such as insecticide-treated bed nets, and (10) innovative (thinking ‘out of the box’) interventions. High levels of retention on ART are vital for individual patients, for credibility of programmes and for on-going resource and financial support.